2020
DOI: 10.1021/acsanm.0c02499
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabright Silica-Coated Organic Nanocrystals for Two-Photon In Vivo Imaging

Abstract: Herein, we demonstrate the potential of ultrabright fluorescent silica-coated organic nanocrystals for two-photon in vivo imaging. These unique nanoparticles (NPs) containing a crystalline core of small push-pull dipolar dye are specifically designed to exhibit two-photon absorption for 2 fluorescence imaging. The NPs can be easily functionalized using click chemistry in pure water, with preservation of the organic core. A novel small-volume DLS technique was used to evaluate the effect of PEGylation on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…[129] In 2020, Perdoor et al were able to observe the in vivo transcranial flow of individual NPs through the bloodstream 30 seconds after injection in a mouse. [130] In another study, Alifu et al showed that twophoton fluorescence imaging can be used for in vivo tracking of organic NPs up to 1200 µm in the brain blood vessels of a mouse. [131] These two studies look very promising for in vivo use, as 2-PFM can be employed either for imaging ear blood vessel or for brain blood vessels.…”
Section: Two-photon Fluorescence Microscopy (2-pfm)mentioning
confidence: 99%
“…[129] In 2020, Perdoor et al were able to observe the in vivo transcranial flow of individual NPs through the bloodstream 30 seconds after injection in a mouse. [130] In another study, Alifu et al showed that twophoton fluorescence imaging can be used for in vivo tracking of organic NPs up to 1200 µm in the brain blood vessels of a mouse. [131] These two studies look very promising for in vivo use, as 2-PFM can be employed either for imaging ear blood vessel or for brain blood vessels.…”
Section: Two-photon Fluorescence Microscopy (2-pfm)mentioning
confidence: 99%
“…Early diagnosis is crucial to successful treatment of cancer, among which early detection of cancerous lesions heavily relies on the development of medical imaging technology. Each imaging modality has a specific advantage and shortcoming, so ongoing nanoprobe research studies focus on combining and exploiting the advantages of diverse nanoprobes to achieve a more accurate and reliable diagnosis . Dual-modal optical-magnetic molecular imaging combines high-sensitivity optical imaging with high-resolution magnetic resonance imaging (MRI), enabling an accurate diagnosis of early stage tumors and comprehensive quantitative analyses of pathophysiological processes in vivo . The fusion of MRI and optical imaging usually brings together a paramagnetic contrast agent for enhanced MRI and a molecular probe for optical imaging. As an example, rare-earth-doped Gd-based nanoparticles have been developed into a potent bifunctional molecular probe due to their ability to enhance MRI contrast and enable optical targeting and tracking simultaneously. , Almutairi et al reported lanthanide-based core–shell–shell nanoparticles as a multimodal contrast agent that can achieve simultaneously enhanced MR/photoluminescence performance, as compared to its individual stand-alone structures .…”
Section: Introductionmentioning
confidence: 99%